How is educational legislation mirrored in textbooks? A mixed-method study in relation to the minimum contents of music education in Early Childhood Education (3-6 years). - Mateos-Moreno, Daniel; Gallego García, Cristina Isabel (Universidad de Valencia, 2022)
Although there are many works dedicated to the study of either educational legislation or textbooks, only a few are devoted to their joint research. In the present study, we aimed to investigate how the national regulations regarding the mandatory contents related to music in Early Childhood Education in the stage of 3 to 6 years are reflected in textbooks in Spain. By means of a multistage mixed methodology, including analyses based on grounded theory, content analysis, as well as cluster and variance analyses, our results provide evidence for: 1) a modern music education philosophy underlying the national Spanish regulations, 2) discrepancies between this philosophy and its development in textbooks, and 3) the existence of different publisher profiles regarding the treatment of contents in music. Finally, we discuss the implications of our results regarding the use of textbooks at this educational stage and in relation to music education.
¿Cómo se refleja la legislación educativa en los libros de texto? Un estudio de metodología mixta en relación a los contenidos mínimos de educación musical en el segundo ciclo (3-6 años) de Educación Infantil
Keywords: Investigación activa en educación; Música - Estudio y enseñanza; Music; Education; Text-books; Childhood; Legislation